Integrating Artificial Intelligence into the Shoe Design Process - Prodromos Minaoglou; Anastasios Tzotzis; Nikolaos Efkolidis; Panagiotis Kyratsis (Engineering Proceedings)
Artificial intelligence (AI) is a branch of computer science that deals with the adoption of human behavioral elements in computer-based systems. Some of these systems support learning, understanding, making inferences, and adaptability. In recent years, artificial intelligence has brought a rapid technological revolution to many different sectors of industry. It is a tool that can greatly influence the different stages of the design process. In this particular study, the goal was to integrate AI into the design process of a product, and more specifically of a soccer shoe, using additive manufacturing technology as a prototyping method. Different stages to be followed during the design of a product include mind mapping, digital sketches, Computer-Aided Design (CAD), rendering, and prototyping, both digital and physical. By integrating AI tools into the traditional design process, designers can enhance the outcomes of their final products through the use of automation and control systems based on a holistic approach to industrial design. This paper introduces a distinct and innovative design framework that combines the benefits of AI digital applications with the expertise of the designer. The proposed design methodology will be used to create a prototype of the designed soccer shoe using rapid prototyping tools for user feedback on its form. The conclusions of the study are that AI is a tool that can be integrated into the design process of a product, improving it, while at the same time supporting the designers’ creativity and innovation.